Implementasi Prinsip Good Governance Dalam Pengelolaan Dana Desa Studi Kasus Di Kabupaten Kuningan: Implementation of Good Governance Principles in Village Fund Management: A Case Study of Kuningan Regency - Rifa'i, Iman; Yuhandra, Erga; Budiman, Haris; Akbar, Satria; Asiyah, Mina Rabiatul (UIN Kiai Haji Ahmad Sidiq Jember, 2025)
Village Fund policies have undergone regulatory changes to strengthen fiscal governance, yet their implementation remains hindered by inconsistencies among national, regional, and village regulations. The weakness of good governance does not stem from a lack of rules, but from misalignment between normative designs and local practices. Accountability is carried out administratively but has not fully reached substantive public oversight, while community participation and access to information remain procedural. Using a normative juridical method, this study formulates two key issues: the principles of good governance as legal foundations for Village Fund management, and the rule of law and oversight mechanisms as instruments to reinforce them. Based on the Village Law and related regulations, the findings show weak legal harmonization and ineffective supervision, resulting in formalistic accountability and suboptimal legal control. Strengthening regulatory synchronization, enhancing village institutional capacity, and internalizing good governance principles are essential to achieving transparent, accountable, and law-based Village Fund governance. Abstrak Kebijakan Dana Desa telah mengalami perubahan regulasi untuk memperkuat tata kelola fiskal, namun implementasinya masih terganggu oleh disharmoni antara regulasi nasional, daerah, dan desa. Lemahnya good governance bukan karena kekurangan aturan, tetapi karena ketidaksesuaian antara desain normatif dan praktik lokal. Akuntabilitas berjalan secara administratif namun belum menyentuh pengawasan publik yang substansial, sementara partisipasi dan akses informasi masih bersifat prosedural. Penelitian dengan metode yuridis normatif ini merumuskan dua masalah: prinsip good governance sebagai asas hukum pengelolaan Dana Desa, serta supremasi hukum dan mekanisme pengawasan sebagai instrumen penguatnya. Berbasis UU Desa dan regulasi terkait, hasil penelitian menunjukkan lemahnya sinkronisasi hukum dan pengawasan, sehingga akuntabilitas menjadi formalistik dan kontrol hukum kurang optimal. Diperlukan penguatan harmonisasi regulasi, peningkatan kapasitas desa, dan internalisasi prinsip good governance untuk mewujudkan tata kelola Dana Desa yang transparan, akuntabel, dan berbasis hukum.